Kościół pierwszych wieków wobec problemu dzieci osieroconych i porzuconych - Wygralak, Paweł (Vox Patrum, 2025)
The article discusses the problem of care for orphaned and abandoned children by ancient Christians. Based on the available sources, it is shown that the bishop was responsible for organizing care for such children. It was primarily on his initiative, although sometimes also on the initiative of laymen, that orphanages (orphanotrophia) and homes for abandoned children (brefatrofia) were established. Christian families also took care of these children. Efforts were made to prepare children for adult life. Such activity of Christians was a complete novelty in the ancient world, where there was no systematic care for orphaned and abandoned children.